The Humanities and Social Sciences in the Age of STEM: The Struggle of Japanese as a Linguistic Minority - Yonezawa, Akiyoshi (International Higher Education, 2017)
The author analyzes the background of the recent disputes on the relevance of humanities and social sciences at national public universities in Japan. Based on the analysis, several themes emerge, including long term governmental policies to prioritize STEM fields, and the difficulties of identifying the values of the humanities and social sciences in countries that are linguistically isolated in the age of globalization.